2007
DOI: 10.1016/j.cmet.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

An Afferent Vagal Nerve Pathway Links Hepatic PPARα Activation to Glucocorticoid-Induced Insulin Resistance and Hypertension

Abstract: Glucocorticoid excess causes insulin resistance and hypertension. Hepatic expression of PPARalpha (Ppara) is required for glucocorticoid-induced insulin resistance. Here we demonstrate that afferent fibers of the vagus nerve interface with hepatic Ppara expression to disrupt blood pressure and glucose homeostasis in response to glucocorticoids. Selective hepatic vagotomy decreased hyperglycemia, hyperinsulinemia, hepatic insulin resistance, Ppara expression, and phosphoenolpyruvate carboxykinase (PEPCK) enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…Cutting of the vagus nerve and the effect on insulin release may be compensated by the chronic corticosterone-induced insulin secretion. Bernal-Mizrachi and co-workers showed that dexamethasone-treated rats displayed a disruption of the afferent vagus, glucose intolerance, and hypertension and the vagotomy was able to reverse these effects (Bernal-Mizrachi et al 2007). They consider that glucocorticoid-induced glucose intolerance required intact vagal afferent fibers.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cutting of the vagus nerve and the effect on insulin release may be compensated by the chronic corticosterone-induced insulin secretion. Bernal-Mizrachi and co-workers showed that dexamethasone-treated rats displayed a disruption of the afferent vagus, glucose intolerance, and hypertension and the vagotomy was able to reverse these effects (Bernal-Mizrachi et al 2007). They consider that glucocorticoid-induced glucose intolerance required intact vagal afferent fibers.…”
Section: Figurementioning
confidence: 99%
“…They consider that glucocorticoid-induced glucose intolerance required intact vagal afferent fibers. Indeed, the complete mechanism of glucocorticoids action in stimulated vagus nerve is still not well understood (Bernal-Mizrachi et al 2007). Although, it is important to highlight that intracerebroventricular (ICV) dexamethasone injections in vagotomized rats did not induce increased food intake, BW, or insulin resistance (Cusin et al 2001).…”
Section: Figurementioning
confidence: 99%
“…But other studies showed that vagal stimulation may not induce IS, and that afferent hepatic vagal branch activation may contribute to IR. 9 Additional studies suggested that SCI might affect the response to insulin because of alterations in body composition. The combination of higher fat content and reduced skeletal muscle mass, which are frequent in patients with chronic SCI, may result in pronounced competition between free fatty acids and glucose oxidation, leading to IR.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 8 Interestingly, afferent fibers of the vagus nerve seem to be required for this effect: Selective vagotomy interfered with hepatic PPARα expression and consecutively diminished GCinduced hepatic insulin resistance and hyperglycemia [58,59].…”
Section: Gcs and Hepatic Glucose Metabolismmentioning
confidence: 99%